Oral intake of heat-killed Lactiplantibacillus pentosus ONRICb0240 partially protects mice against SARS-CoV-2 infection - Kiso, Maki; Uraki, Ryuta; Ito, Mutsumi; Yamayoshi, Seiya; Kotani, Yoshifumi; Imai, Masaki; Kohda, Noriyuki; Kawaoka, Yoshihiro (Frontiers in Virology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the ongoing coronavirus pandemic. Besides vaccines and antiviral drugs, probiotics have attracted attention for prevention of SARS-CoV-2 infection. Here, we examined the efficacy of heat-killed Lactiplantibacillus pentosus ONRICb0240 (b240) against SARS-CoV-2 infection in mice. We observed that oral intake of heat-killed b240 did not affect virus titers in the respiratory organs of SARS-CoV-2-infected mice, but did provide partial protection against SARS-CoV-2 infection. In addition, heat-killed b240 treatment suppressed the expression of IL-6, a key proinflammatory cytokine, on Day 2 post-infection. Our results highlight the promising protective role of heat-killed b240 and suggest a possible mechanism by which heat-killed b240 partially protects against SARS-CoV-2 infection by modulating host responses.